De grupos guerrilleros a partidos políticos, un análisis a partir de la cultura política y el desempeño electoral: casos Guatemala y Uruguay. (2019)
IIn Guatemala and Uruguay, there are currently political parties derived from the demobilization of guerrilla groups. These have achieved different levels of success in electoral processes as a possible consequence of their distinctive traits of political culture and their democracies’ characteristics. To contribute to the understanding of the differences between the two cases of study, this article analyzed the relationship between the political culture and the electoral performance of the Unidad Revolucionaria Nacional Guatemalteca -URNG and the Frente Amplio. The aim was to determine how the traits of the political culture have facilitated or hindered the electoral performance of the former guerrilla groups and, therefore, to give an approximation to what the last demobilized guerrillas in Latin America might face.